2015
DOI: 10.1039/c5ra12505g
|View full text |Cite
|
Sign up to set email alerts
|

The promotional role of Ce in Cu/ZSM-5 and in situ surface reaction for selective catalytic reduction of NOx with NH3

Abstract: Cu/ZSM-5 and Ce doped Cu/ZSM-5 catalysts were prepared by the incipient-wetness-impregnation method, and the effect of Ce doping on the structure and the catalytic performance of the Cu/ZSM-5 catalyst was investigated in detail for the selective catalytic reduction (SCR) of NO with NH 3 . The results showed that the addition of Ce can markedly broaden the operation temperature window of the Cu/ZSM-5 catalyst for NH 3 -SCR and enhance its H 2 O and SO 2 resistance. The presence of Ce promoted an enrichment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 44 publications
5
69
0
1
Order By: Relevance
“…4 The observation of a sharp feature at 1606 cm À1 , which could be tentatively attributed to nitratetype species, and subsequently the appearance of NO + (which has been proposed to be formed through the disproportionation of NO 2 ) suggests an important role in the catalytic cycle also for nitrates and nitrites, particularly for completing the Cu redox cycle as has been previously postulated for both NH 3 -SCR in Cu zeolites and observed in hydrogen-promoted hydrocarbon SCR on silver-alumina catalysts. 38,41,42 The exact determination of these features is challenging for conventional operando DRIFTS experiments as the spectra are dominated by species originating from NH 3 . Interestingly the identication of these intermediates indicates a pathway through which gas phase NO 2 can be produced in the cycle to circumvent the need to cofeed it to effect fast SCR as is typical in Fe-based systems.…”
Section: Mechanistic Implications Of the Resultsmentioning
confidence: 99%
“…4 The observation of a sharp feature at 1606 cm À1 , which could be tentatively attributed to nitratetype species, and subsequently the appearance of NO + (which has been proposed to be formed through the disproportionation of NO 2 ) suggests an important role in the catalytic cycle also for nitrates and nitrites, particularly for completing the Cu redox cycle as has been previously postulated for both NH 3 -SCR in Cu zeolites and observed in hydrogen-promoted hydrocarbon SCR on silver-alumina catalysts. 38,41,42 The exact determination of these features is challenging for conventional operando DRIFTS experiments as the spectra are dominated by species originating from NH 3 . Interestingly the identication of these intermediates indicates a pathway through which gas phase NO 2 can be produced in the cycle to circumvent the need to cofeed it to effect fast SCR as is typical in Fe-based systems.…”
Section: Mechanistic Implications Of the Resultsmentioning
confidence: 99%
“…The spectral series can be divided in three regions: the NH 4 + -chemisorption and Lewis acid sites region (1400-2000 cm −1 ), the N-H stretching region (2000-3500 cm −1 ) and the -OH stretching region (3500-4000 cm −1 ). In the first region, the absorption peaks at 1488 [28], 1745 [29,30] and 1946 cm −1 [30] show similar intensities among all samples and they are assigned to NH 4 + adsorbed on BASs. The peak at 1592 cm −1 , assigned to NH 3 adsorbed on Lewis sites [29], is more pronounced in the spectrum of the Al-silicalite sample and almost disappears in the spectrum of the Fe-silicalite sample.…”
Section: Nh 3 Adsorptionmentioning
confidence: 87%
“…The factor being responsible for the superior activity of CeO x^C uO-EE samples could be mainly attributed to the Ce(IV)-Ce(III) and Cu(II)-Cu(I) co-present Ce-O-Cu interactive surface constructed from chemically embedding of Ce into the surface of Cu-based substrate, since the synergistic e®ect present by the transformation of CeðIVÞ þ CuðIÞ $ CeðIIIÞ þ CuðIIÞ during the catalytic cycle has been recognized the main factor to in°uence the surface chemical properties of Ce-O-Cu composited structures such as the acidic feature, the reactivity with reactants and the mobility of active oxygen species, 22,28,[37][38][39][40][41] in turn, these properties would greatly impact on reaction behaviors and govern catalytic performance. 16,45,46 In our case, by modulating and controlling the Ce dosage at 1.6 wt.% for preparing CeO x^C uO-EE structure, the comprehensive surface properties could be manipulated to the optimal level among samples (as disclosed in Table 1), which could be the clue to understand the superior catalytic performance of CeO x (1.6 wt.%)^CuO-EE. Except for the synergistic e®ect, some recent works supposed that the modi¯cation of Ce to Cu based catalysts for NH 3 -SCR of NO could be attributed to the stimulation for producing isolated Cu 2þ .…”
Section: Tof ¼ ðPv =Rt þX Nmentioning
confidence: 99%
“…As disclosed by the previous structure characterizations, the co-existence of redox pairs of Ce(IV)-Ce(III) and Cu(II)-Cu(I) and the relative concentrations of involved metal ions in surface layers were manipulated with introducing and increasing Ce dosage among CeO x^C uO-EE samples, which could be the direct origins for the acidic properties and corresponding changes observed on them, since the involved metal ions such as Ce 3þ or Cu þ could act as Lewis acid sites and their distributions would directly impact on the interaction with NH 3 . 45,46 In addition, it should be noted that such dramatic changes in surface acid properties among CeO x^C uO-EE samples were based on the subtle increase of Ce loading in a low range (0.83-2.3 wt.%), in view of that the acid property especially the property of Lewis acid site was believed to be the crucial factor to govern the NH 3 selective catalytic reduction process of NO x , 19,47 the phenomenon indicated that the chemical embedding strategy employed in this work was feasible to prepare oxide composites in not only directly adjusting the interactive surface structures but also sensitively manipulating their chemical reactivities. According to NH 3 -TPD pro¯les, the quantitative desorption amount of NH 3 was resolved to estimate the acid site number over samples, as collected in Table 1.…”
Section: -11mentioning
confidence: 99%